THE SOUND HOREG PHENOMENON: Between Entertainment and Social Disturbance - Armayanto, Harda; Sahidin, Amir; Khasanah, Neneng Uswatun (UIN Sumatera Utara, 2025)
The phenomenon of sound horeg, characterized by the use of high-powered sound systems in public entertainment, has become widespread in Indonesia, particularly in East Java. While it is often perceived as a form of cultural expression and community entertainment, it also raises social concerns due to noise disturbances. This study examines sound horeg from social and cultural perspectives using the framework of Religious Moderation. Employing a library research method, this study analyzes academic literature, news reports, and relevant documents. The findings indicate that Religious Moderation offers a balanced analytical framework; the principle of justice requires equal treatment of all forms of public entertainment; and the principle of balance is essential to harmonize cultural values, economic interests, environmental sustainability, public health, and religious considerations. Properly managed, sound horeg has the potential to strengthen social cohesion and preserve local wisdom without falling into extremes.Keywords: Sound horeg, religious moderation, society, culture